2020
DOI: 10.1029/2019ja027062
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Alfvén Waves From Magnetotail to the Ionosphere in Global Hybrid Simulation Associated With Fast Flows

Abstract: We have used the Auburn Global Hybrid Code in 3‐D to study the generation, dynamics, and global structure of kinetic Alfvén waves (KAWs) from the magnetotail to the ionosphere. Our results show that KAWs are generated in magnetic reconnection in the plasma sheet, located around fast flows, and carrying transverse electromagnetic perturbations, parallel Poynting fluxes, parallel currents, and parallel electric field. Overall, shear Alfvénic turbulent spectrum is found in the plasma sheet. The KAWs are shear Alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 71 publications
3
57
0
Order By: Relevance
“…However, in the case of kinetic Alfvén waves, the Walen relation for scales much larger than the electron inertial length is (L. Cheng et al, 2020)  …”
Section: Turbulent Heating Estimatementioning
confidence: 99%
“…However, in the case of kinetic Alfvén waves, the Walen relation for scales much larger than the electron inertial length is (L. Cheng et al, 2020)  …”
Section: Turbulent Heating Estimatementioning
confidence: 99%
“…KAWs as a natural mode of Alfven waves in hot ion plasma (Stasiewicz et al, 2000) are suggested to be generated by several different mechanisms, e.g., mode conversion (Hasegawa and Chen, 1975;Hasegawa, 1976;Lin et al, 2012;Johnson and Cheng, 1997), phase mixing (Guo et al, 2015) and magnetic reconnection (Chaston et al, 2005(Chaston et al, , 2009Liang et al, 2016;Wang et al, 2019b;Cheng et al, 2020). These waves are believed to be responsible for energy transfer from the magnetotail to 10 -1 10 0 10 1 10 2…”
Section: Discussionmentioning
confidence: 99%
“…The solar wind ion temperature is T 0 = 10 eV. This case has previously been studied by Lin, Wang, et al (2014); ; L. Cheng, Lin, et al (2020) for various properties of fast flows in the magnetotail using ANGIE3D. Figure 1 shows the global view of magnetic field strength B at simulation time t = 00:58:27, approximately 1 h after the impact of the solar wind on the magnetosphere, obtained from the global hybrid simulation, together with some typical magnetic field lines (orange solid line).…”
Section: -D Global Hybrid Modelmentioning
confidence: 96%
“…(2014) and L. Cheng, Lin, et al. (2020). A typical time step interval for advancing particles is normalΔt=0.050.3333emnormalΩ01, within which a subcycling of 10 steps is applied to the magnetic field update.…”
Section: Simulation Modelmentioning
confidence: 99%